Creating and Sustaining Safe and Inclusive Spaces for LGBTQ Youth: An Exploratory Investigation of the Role of Educational Professionals - Luceno, Andrew; Andrews, Dr. John (Jac); Strong, Dr. Tom (Alberta Journal of Educational Research, 2022)
Educators can play a critical role in buffering LGBTQ youth from potential victimization. As such, the present study explored the following questions: 1) What are the roles of educators (i.e., teachers, school administrators) with respect to promoting and creating safe and inclusive spaces for LGBTQ youth; 2) what unique contributions can educators make in nurturing those spaces; and, 3) what barriers do educators face in creating safe and inclusive spaces for LGBTQ youth? This study used a convergent parallel design mixed-methods approach. Descriptive statistics were gathered from survey results; the interview data was analyzed using thematic analysis in order to generate themes relevant to the research questions. Discussion focuses on the roles of educators and the barriers with respect to providing safe and inclusive spaces for LGBTQ youth. The paper concludes with empirical and practical implications of the study. Key words: LGBTQ, teachers, administrators, support, advocacy Les professionnels de l’éducation peuvent jouer un rôle essentiel en protégeant les jeunes LGBTQ d'une victimisation potentielle. Ainsi, la présente étude s'est penchée sur les questions suivantes : 1) Quels sont les rôles des professionnels de l’éducation (c'est-à-dire des enseignants et des administrateurs scolaires) en ce qui concerne la promotion et la création d'espaces sûrs et inclusifs pour les jeunes LGBTQ ? 2) Quelles contributions uniques les professionnels de l’éducation peuvent-ils apporter à la création de ces espaces ? 3) Quels obstacles les professionnels de l’éducation rencontrent-ils dans la création d'espaces sûrs et inclusifs pour les jeunes LGBTQ ? Cette étude a utilisé une approche mixte de méthodes convergentes et parallèles. Des statistiques descriptives ont été recueillies à partir des résultats de l'enquête ; les données des entretiens ont été analysées à l'aide d'une analyse thématique afin de générer des thèmes pertinents pour les questions de recherche. La discussion porte sur les rôles des professionnels de l’éducation et les obstacles à la création d'espaces sûrs et inclusifs pour les jeunes LGBTQ. L'article se termine en présentant les implications empiriques et pratiques de l'étude. Mots cles: LGBTQ, enseignants, administrateurs, soutien, plaidoyer